The Impact of the European Convention of Human Rights on the Polish Legal System - Wiśniewski , Adam (Polish Review of International and European Law, 2020)
As of the year 2018, a quarter of a century had passed since Poland became a party to the European Convention on Human Rights. Therefore, this year provides a good opportunity to reflect on this Convention’s impact and significance as regards the Polish legal system. Poland’s accession to the Council of Europe and the ratification of the Convention took place in a relatively short period of time. Unfortunately, it was not accompanied by any planned and systemic review of the national legislation with a view of ensuring its compatibility with the requirements of ECHR. After more than 40 years of Poland’s membership in the so-called eastern block dominated by the USSR and the experience of being governed by an undemocratic political system based on the dictatorship of one party, on could hardly expect that the Polish legal system could be effectively adapted to the standards of the most advanced system of international protection of human rights ECHR in two or three years. This resulted, inter alia, in a relatively large number of complaints against Poland shortly after Poland recognized the competence of the Commission of Human Rights and ECtHR to receive individual complaints against Poland, as well as, in pilot judgments such as in the Broniowski case, in which ‘widespread problems resulting from a malfunctioning of Polish legislation and administrative practice and which has affected and remains capable of affecting a large number of persons’ was identified. Hundreds of judgments against Poland given by the Strasbourg Court in which violations were found have revealed a variety of problems in the Polish legal system and practice. As the result of considerable efforts to address these judgments, the Polish system of law is being continuously transformed in order to ensure it is in line with ECHR’s human rights standards. The implementation of Strasbourg’s judgments involves a number of general measures that need to be taken, including not only changes in the legislation, but also changes in practice, in the law’s interpretation and the manner it is applied. The rising awareness of the Strasbourg standards among judges, police officers, officials, etc. is of crucial importance for ensuring the proper enactment of the Court’s judgments. Poland used to be singled out among countries in which ‘major structural problems concerning cases in which extremely worrying delays in implementation have arisen’. Fortunately, in recent years some progress in the enforcement of ECtHR’s judgments has been achieved, with the number of unimplemented judgments being significantly reduced. Nevertheless, given the unsystematic verification of the compatibility of the Polish legal system with the ECHR through the instrument of individual complaint, a more systemic approach to ensuring this compatibility is needed. One of such mechanisms could be the introduction of preventive control of draft laws with the Convention in the light of the case-law of the Court.